Thermal and Electrical Conductivities of Very-High-Purity Indium - de la Cruz, M.E.; Cotignola, J.M.; Bressan, O.J.; Luengo, C.A. (American Physical Society, 1968)
Fil: de la Cruz, M.E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Brown University. Department of Physics; Estados Unidos